Aortic arch variant with a common origin of the innominate and left carotid artery as a determinant of thoracic aortic disease: a systematic review and meta-analysis. (16th October 2019) - Marrocco-Trischitta, Massimiliano M; Alaidroos, Moad; Romarowski, Rodrigo M; Milani, Valentina; Ambrogi, Federico; Secchi, Francesco; Glauber, Mattia; Nano, Giovanni
Abstract: The aim of this study was to investigate whether the 'bovine' arch [i.e. arch variant with a common origin of the innominate and left carotid artery (CILCA)] is associated with an increased risk of thoracic aortic disease (TAD). The study was conducted according to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. The PubMed, EMBASE and Cochrane databases were searched to identify all case series reporting about CILCA arch and TAD between January 2008 and December 2018. A total of 485 studies were screened. The prevalence of CILCA arch was assessed, and data analysis was performed considering the difference in the risk of TAD for presence versus absence of CILCA arch. Eight studies enrolling 11 381 subjects were retrieved for quantitative analysis. The proportion of TAD among CILCA arch patients was higher [41.5% (28.1–56.4)] than the proportion among patients with standard arch configuration 34.0% (20.1–51.4). The odds ratio of developing TAD was 1.4 times higher in subjects with CILCA arch (95% confidence interval 1.068–1.839). The test for an overall effect indicated a significant association between CILCA arch and TAD ( P < 0.015). The I 2 was 78.1% with a value of P < 0.001 for heterogeneity. The Egger test did not show evidence of publication bias ( P = 0.317). In conclusion, our meta-analysis supports the hypothesis of a correlation between the presence of CILCA arch and the onset of TAD. Our results warrant a specific and long-term surveillance for patients with this anatomical variant, and a thorough awareness of its potential clinical implications during image interpretation.